HUBUNGAN PENGETAHUAN IBU DENGAN TINGKAT STUNTING DI WILAYAH KERJA UPT PUSKESMAS PATUK I - Khoeriyah, Salis Miftahul (Jurnal Kesehatan Samodra Ilmu (JKSI), 2024)
Background: Stunting is a nutritional problem in the world, one of the factors influencing stunting is knowledge. Insufficient knowledge can result in poor parenting patterns, thus affecting the incidence of stunting in toddlers. Mothers with low knowledge have a 10,2 times greater risk of their children experiencing stunting compared to mothers with sufficient knowledge. The knowledge that parents have about the signs and symptoms that appear is one way to prevent stunting. If parental knowledge is good then the parents’ sense of awareness about stunting prevention can be implemented. Objective: To determine the relationship between mother knowledge and the level of stunting in toddlers at the UPT Puskesmas Patuk I Methods: This research is quantitative research, the research design used is cross sectional. The sample in this study was 52 mothers who had stunted toddlers at the UPT Puskesmas Patuk I. The instrument of this research was to use a questionnaire and analyzed using a bivariate test Spearman Rank. Results: The level of knowledge of the 52 respondents regarding the incidence of stunting, most of them were at the level of sufficient knowledge was 25,0% and the level of good knowledge was 23,1%. Meanwhile, the incidence of stunting was mostly short 76,9% and very short, 23,1%. Conclusions: There is a relationship between maternal knowledge and the level of stunting tin the UPT Puskesmas Patuk I work area, with a P value of 0,001, thus H1 is accepted while H0 is rejected